Effects of Acupuncture in Anesthesia for Craniotomy: A Meta-Analysis. Issue 3 (July 2017) - Asmussen, Sven; Maybauer, Dirk M.; Chen, Jiande D.; Fraser, John F.; Toon, Michael H.; Przkora, Rene; Jennings, Kristofer; Maybauer, Marc O.
Abstract : Background: Acupuncture treatment has been used in China for >2500 years, and at present it is used worldwide as a form of analgesia in patients with acute and chronic pain. Furthermore, acupuncture is regularly used not only as a single anesthetic technique but also as a supplement or in addition to general anesthesia (GA). Objectives: The aim of this systematic review and meta-analysis was to assess the level of evidence for the clinical use of acupuncture in addition to GA in patients undergoing craniotomy. Design: This is a systematic review of randomized controlled trials with meta-analyses. Data Sources: The literature search (PubMed, Cochrane Library, and Web of Science) yielded 56 citations, published between 1972 and March 01, 2015. No systematic review or meta-analyses on this topic matched our search criteria. Each article of any language was assessed and rated for the methodological quality of the studies, using the recommendation of the Oxford Centre for Evidence Based Medicine. Ten prospective randomized controlled clinical trials with a total of 700 patients were included. Eligibility Criteria: Included in the meta-analysis were studies that involved any craniotomy under GA compared with a combination of GA and acupuncture. Exclusion criteria were no acupuncture during surgery, no GA during surgery, only postoperative data available, animal studies, and low grade of evidence. Results: The use of acupuncture significantly reduced the amount of volatile anesthetics during surgery ( P <0.001) and led to faster extubation time ( P =0.001) and postoperative patient recovery ( P =0.003). In addition, significantly reduced blood levels of the brain tissue injury marker S100β 48 hours after operation ( P =0.001) and occurrence of postoperative nausea and vomiting ( P =0.017) were observed. No patient studied suffered from awareness. Conclusions: The analysis suggests that the complementary use of acupuncture for craniotomy has additional analgesic effects, reduces the needed amount of volatile anesthetic, reduces the onset of postoperative nausea and vomiting, and might have protective effects on brain tissue. Our findings may stimulate future randomized controlled trials to provide definitive recommendations.